The Inclusive Practices Tools: Trying to Take a Short Cut to Inclusion? - Christopher McMaster (New Zealand Journal of Teachers' Work)
The Ministry of Education, through the New Zealand Council for Educational Research (NZCER), is currently trialling the Inclusive Practices Tools (IPT), an auditing device in which schools can measure the extent of ‘inclusive practice’ and identify areas for improvement. IPT will be rolled out nationally beginning in late 2014. Through reducing the exploration of inclusive values to a streamlined analysis of practice, there emerges the threat of limiting the aspirations of the project of inclusion. Lacking in the ‘tools’ offered to schools are essential aspects of sustainable change and professional development, notably time, reflection, stakeholder involvement, and collective exploration of values and assumptions. However, despite being handed what can be seen as a limited set of tools, teachers may use the opportunity to create more inclusive schools, and suggestions are offered in how to make the IPT review process more meaningful for the school community.